Sub-millimetre accurate human hand kinematics: from surface to skeleton. Issue 2 (25th January 2018) - Ma'touq, Jumana; Hu, Tingli; Haddadin, Sami
Abstract : A highly accurate human hand kinematics model and identification are proposed. The model includes the five digits and the palm arc based on mapping function between surface landmarks and estimated joint centres of rotation. Model identification was experimentally performed using a motion tracking system. The evaluation of the marker position estimation error, which is on sub-millimetre level across all digits, underlines model quality and accuracy. Noticeably, with the development of this model, we were able to improve various modelling assumptions from literature and found a basic linear relationship between surface and skeleton rotational angles.